Design of Model Predictive Torque Control (MPTC) for Speed Control 3 Phase Induction Motor with Robust Stator Flux Observer - Mudia, Halim; Rameli, Mochammad; Efendi, Rusdhianto (IPTEK Journal of Proceedings Series, 2015)
The induction motor is a desirable alternative to the direct current motor in many applications because it is rugged, reliable and economical. However, control of the induction motor is more complex than the direct current motor, this is caused by the complexity of the dynamics of the induction motor, so the algorithm of induction motor is more complex. Based on these problem, author conducted a study on the induction motor using Model Predictive Torque Control (MPTC) with robust stator flux observer, in which robust stator flux observer is designed to overcome the shortcomings in the Direct Torque Control (DTC) conventional which can cause high fluctuation in flux ripple and torque ripple when reach steady state condition. So from the purpose of the proposed method, the results of the designed system can adjust the rotating speed of the induction motor in accordance references given at 120 rad/s with a settling time is 0.753 seconds, and also can minimize fluctuations in flux ripple and torque.